(untitled) (Zoological Records and Reviews, 2023)
Cave ecosystems – encompassing limestone karst caves, granite boulder caves, sandstone rock shelters, and lava tube systems – represent some of Earth’s most extreme and biologically distinctive habitats, harbouring highly specialised fauna adapted to permanent darkness, reduced food inputs, high humidity, and stable temperatures. Peninsular India, with its extensive limestone formations in Andhra Pradesh and Telangana, granite inselberg complexes across the Deccan, and basalt lava formations of the Deccan Traps, hosts a significant but poorly documented cave fauna. This study presents the first systematic multi-cave, multi-taxon biodiversity assessment of cave-dwelling organisms from 28 cave systems across peninsular India, encompassing troglobitic (obligate cave-dwelling), troglophilic (facultative cave-dwelling), and trogloxenic (cave-visiting) fauna surveyed using standardised transect searches, pitfall arrays, and bat acoustic monitoring. A total of 184 animal species are documented, including 42 troglobitic species representing obligate cave specialists. Eighteen species are candidate new species, all obligate cave-dwellers from limestone karst systems. Bat diversity is the highest component with 28 species documented across all cave types. Cave area, degree of isolation, and substrate type are the strongest predictors of troglobitic species richness. Twelve species are IUCN Threatened. Quarrying, tourism, and guano mining are identified as the primary threats to peninsular Indian cave biodiversity.